Development and content validation of the Urethroplasty Training and Assessment Tool (UTAT) for dorsal onlay buccal mucosa graft urethroplasty. (29th April 2020) - Jasionowska, Sara; Shabbir, Majed; Brunckhorst, Oliver; Khan, Muhammad Shamim; Manzoor, Hussain; Dasgupta, Prokar; Anderson, Paul; Barbagli, Guido; Ahmed, Kamran
Abstract : Objectives: To develop and validate the Urethroplasty Training and Assessment Tool (UTAT) using Healthcare Failure Mode and Effect Analysis (HFMEA) for training and assessment of urology trainees learning this urethral reconstruction technique, as urethroplasty is the 'gold standard' treatment for long and recurrent urethral strictures and with a variety of techniques and a lack of standardised reconstructive curricula, there is a need for procedure‐specific training tools to improve surgeon training and patient safety. Materials and Methods: This international observational study was performed over an 11‐month period. The HFMEA was used to identify and evaluate hazardous stages of urethroplasty to develop the UTAT. Hazard scores were calculated for the included steps of urethroplasty. Content validation was performed by 12 expert surgeons and multidisciplinary teams from international tertiary centres. Results: The HFMEA process resulted in an internationally validated UTAT. Hazard scores ≥4 and single point weaknesses were included to implement actions and outcome measures. Content validation was achieved by circulating the process map, hazard analysis table, and developed tools. Changes were implemented based on the feedback received from expert surgeons. The content validated dorsal onlay buccal mucosa graft bulbar UTAT contained five phases, 10 processes and 23 sub‐processes. Conclusions: The modular UTAT offers a comprehensive validated training tool developed via a detailed HFMEA protocol. This may be utilised to standardise the training and assessment of urology trainees.